The Analysis Study of Effectiveness and Diagnostic Performance of Magnetic Resonance Imaging for Early Identification of Chronic Kidney Disease : A Comprehensive Systematic Review - Audhi, Muhammad Riefki (International Medical Journal Corp. Ltd, 2024)
Background: Chronic kidney disease (CKD) is a global health and economic burden and a raising cause of global deaths. Functional magnetic resonance imaging (fMRI) has been used to evaluate renal oxygenation and fibrosis. The aim of this study to show about effectiveness and diagnostic performance of magnetic resonance imaging for early identification of chronic kidney disease. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Conclusion: MRI biomarkers may be able to pick up early signs of disease progression that have not yet led to a discernible effect on markers in blood and urine. MRI is the only technique able to study the renal medulla in vivo, an area that may play an important role in the pathogenesis of CKD and AKI.